2000
DOI: 10.1081/cbi-100102116
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Extraocular Light to Facilitate Circadian Rhythm Reentrainment in Humans

Abstract: Although extraocular light can entrain the circadian rhythms of invertebrates and nonmammalian vertebrates, almost all studies show that the mammalian circadian system can only be affected by light to the eyes. The exception is a recent study by Campbell and Murphy that reported phase shifts in humans to bright light applied with fiber-optic pads behind the knees (popliteal region). We tested whether this extraocular light stimulus could accelerate the entrainment of circadian rhythms to a shift of the sleep s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 43 publications
6
24
1
Order By: Relevance
“…The direction and magnitude of DLMO and CBT minimum phase shifts also were positively related, demonstrating a direct effect on the circadian timing system, similar to other studies (8,18,20,23,30,39,58). DLMO occurred a little over 7 h before CBT minimum, at baseline and after exposure, with a positive relationship between the two markers, as has been reported previously (7,9,14,23).…”
Section: Discussionsupporting
confidence: 71%
“…The direction and magnitude of DLMO and CBT minimum phase shifts also were positively related, demonstrating a direct effect on the circadian timing system, similar to other studies (8,18,20,23,30,39,58). DLMO occurred a little over 7 h before CBT minimum, at baseline and after exposure, with a positive relationship between the two markers, as has been reported previously (7,9,14,23).…”
Section: Discussionsupporting
confidence: 71%
“…A similar conclusion was reached by Eastman et al (54) based on results from a study using light exposure devices identical to those employed by Campbell and Murphy (48). Healthy young adults, the popliteal regions of whom were exposed for 3h to either about 13,000 lux or to no light, showed no systematic differences in the degree to which rhythms of salivary melatonin and body core temperature were shifted relative to baseline measures.…”
Section: Eocp In Vertebrates 151supporting
confidence: 61%
“…The time between the baseline DLMO and the start of the 1st morning bright light pulse was 8.6 ± 1.5 h in the continuous light group and 9.2 ± 1.2 h intermittent light group, but these were not significantly different, [t(17) = -0.97, p = 0.35]. Several studies have shown that the average interval between the DLMO and the Tmin is 7 h (e.g., Cagnacci et al, 1996;Brown et al, 1997;Eastman et al, 2000). Thus, we estimate that the interval between the baseline Tmin and the start of the 1st bright light pulse was 1.5 to 2 h (remember wake time on 1st day of treatment was 1 h earlier than baseline).…”
Section: Resultsmentioning
confidence: 99%